POTENSI PRODUKSI PLTS ATAP GEDUNG RUSUNAWA UNIVERSITAS UDAYANA - Partogi Manalu, Eli Musa Reja; Ariastina, Wayan Gede; Dwi Giriantari, Ida Ayu; Setiawan, I Nyoman; Sukerayasa, I Wayan; Satya Kumara, I Nyoman (Jurnal SPEKTRUM, 2023)
The government will continue to increase the use of new and renewable energy as a solution to meet electricity needs, one of which is the use of rooftop solar power plants. In this research, the location that will be planned to install rooftop PV solar system is the Udayana University Rusunawa Building. The produced energy will be able to meet the electrical energy need and as well as supporting the government programs in the utilization of new and renewable energy. The capacity of the rooftop PV solar system to be installed is determined based on the load profile of the Udayana University Rusunawa Building. Three different scenarios namely 20 kW, 15 kW and 10 kW PV solar systems have been simulated using a PV solar simulator. Results of the simulation scenarios then are compared to look at the differences among the produced energy.